A longitudinal analysis of ethnic unemployment differentials in the UK. Issue 5 (3rd April 2020) - Longhi, Simonetta
ABSTRACT: As in many developed countries, in the UK the unemployment rate of ethnic minorities is higher than the unemployment rate of the white British majority. These differences may be due to a higher probability of ethnic minorities entering unemployment by losing a job, or to a lower probability of exiting unemployment by finding a job. Using Understanding Society, the UK Household Longitudinal Study, this paper analyses what individual and job characteristics contribute to job loss, what contribute to job finding, and to what extent ethnic unemployment differentials can be explained by such characteristics. For both men and women the results show no relevant ethnic differences in the probability to transition from a paid job into unemployment. Only Indian UK born women seem more likely to transition than white British majority women, while for other groups the small differences are in favour of ethnic minorities. Segregation in occupations characterised by low wages and less stable jobs does not seem to contribute to the higher unemployment rate of ethnic minorities. The main determinant of ethnic unemployment differentials seems to be the longer duration of unemployment for ethnic minorities, which, however, remains largely unexplained after the inclusion of individual and household characteristics.